Organizational climate in the human talent of the hospital institutions, Manabi - Ecuador - Zambrano Montesdeoca, Lady (2018)
The investigation determined the influence of the Organizational Climate on the Human Talent of the Hospital Institutions of the Province of Manabí - Ecuador in 2015. For the study of this area of management, an analysis of both variables is developed applying different techniques and instruments adapted to the particularities of the case study. Identifying which components affect it and how they can be perfected. From this, improving the Organizational Climate to obtain a better performance of Human Talent. The design of the research is non-experimental / descriptive, correlational, quantitative and transversal. As a result, the Organizational Climate influences the Human Talent of the Hospital Institutions, understanding that the work environment influences its performance and satisfaction. The Rules and Regulations facilitate the Division of positions and Salaries, which allows skill in the performance of work. The decision making of workers is closely related to responsibility. The Work Standards influence the service provided by employees to users and workers are rewarded for the work they do, receiving fair and respectful treatment.